Reviewing Ancient History: identities, integration and other contemporary approaches - Costa, Alex Aparecido da (Romanitas - Revista de Estudos Grecolatinos, 2016)
Review of: GUARINELLO, Norberto Luiz. História Antiga. São Paulo: Contexto, 2014. 174 p.
Keywords: Ancient History; Historiography; Identities